Determining the burden of fungal infections in Zimbabwe - Pfavayi, LT; Denning, DW; Baker, S; Sibanda, EN; Mutapi, F (Springer Nature, 2021)
Zimbabwe currently faces several healthcare challenges, most notably HIV and associated infections including tuberculosis (TB), malaria and recently outbreaks of cholera, typhoid fever and COVID-19. Fungal infections, which are also a major public health threat, receive considerably less attention. Consequently, there is dearth of data regarding the burden of fungal diseases in the country. We estimated the burden of fungal diseases in Zimbabwe based on published literature and ‘at-risk’ populations (HIV/AIDS patients, survivors of pulmonary TB, cancer, chronic obstructive pulmonary disease, asthma and patients receiving critical care) using previously described methods. Where there was no data for Zimbabwe, regional, or international data was used. Our study revealed that approximately 14.9% of Zimbabweans suffer from fungal infections annually, with 80% having tinea capitis. The annual incidence of cryptococcal meningitis and Pneumocystis jirovecii pneumonia in HIV/AIDS were estimated at 41/100,000 and 63/100,000, respectively. The estimated prevalence of recurrent vulvovaginal candidiasis (RVVC) was 2,739/100,000. The estimated burden of fungal diseases in Zimbabwe is high in comparison to other African countries, highlighting the urgent need for increased awareness and surveillance to improve diagnosis and management.